Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Insurance Sector-Regulation, Supervision, Recovery, and Resolution Regime Prospects. (IMF Staff Country Reports; Country Report ;, 2020)
This review provides an update on the Austrian insurance sector and an analysis of certain key aspects of the regulatory and supervisory regime. The note analyzes regulation and supervision in relation to key issues identified in previous Financial Sector Assessment Programs (FSAP), as well as material changes since the last FSAP. This note also covers the current situation and potential changes in the crisis management and early intervention framework of the insurance sector. It focuses on issues relevant to a long-standing policyholder protection mechanism, early intervention powers-existing and under discussion-and crisis management and resolution arrangements for insurance companies and groups. The analysis recommends that proper implementation of Solvency II needs ongoing validation and scrutiny by regulators, which could be at risk if supervisory resources with skills and expertise are not retained. Higher legal, reputational, and conduct risks are posing additional pressures to the life insurance sector. Market conduct supervision should be enhanced, with active use of enforcement powers in addition to the insights that studies launched by the government will provide.